The Economic Functions of a City in Relation to Its Size - Clark, Colin (Econometrica, 1945)
All economic activity can usefully be classified under three heads, namely: (i) Direct exploitation of natural resources (agriculture, pasture, forestry, fishing, hunting and trapping, mining and quarrying, hydroelectric power). (ii) Manufacture, which may be precisely defined as the organised labour of a number of workers using mechanical power for the purpose of continuously producing transportable goods. (This definition thus excludes, for instance, the workshop employing only one or two workers, the dressmaker who does not use mechanical power, the builder whose product is not transportable.) (iii) All other activities, which may be described for convenience as the Service Industries. The principal service industries are building and construction, commerce, transport, education, public administration, and the like. This classification must form the starting point for any scientific theory of the location of economic activities and of the functions of cities. For the first group of industries must, by their nature, be carried on where the natural resources are located. The manufacturing industries, on the other hand, producing, by definition, goods that are transportable, and using as materials either natural products or partially manufactured goods that are also transportable, can generally be carried on, if desired, at a point distant both from their consumers and from their suppliers of materials. (If either the product or the materials are particularly bulky, perishable, or otherwise difficult to transport, this freedom is of course diminished, but does not disappear.) The service industries, however, diverse though they may be in other respects, all share the fundamental characteristic that they can on the whole only be carried out in the city where the consuming population lives, or at least at some centre that the consuming population can reach without undue difficulty. A community at any given level of average income expects to consume services up to a certain standard